2007
DOI: 10.1140/epjb/e2007-00343-8
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic exchange models for income and wealth distributions

Abstract: Abstract. Increasingly, a huge amount of statistics have been gathered which clearly indicates that income and wealth distributions in various countries or societies follow a robust pattern, close to the Gibbs distribution of energy in an ideal gas in equilibrium. However, it also deviates in the low income and more significantly for the high income ranges. Application of physics models provides illuminating ideas and understanding, complementing the observations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
257
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 205 publications
(270 citation statements)
references
References 70 publications
9
257
0
Order By: Relevance
“…Subsequent studies have revealed that the distributions of income and wealth possess some globally robust features (see, e.g., [7]): the bulk of both the income and wealth distributions seem to reasonably fit both the log-normal and the Gamma distributions. Economists have a preference for the log-normal distribution [15,16], while statisticians [17] and physicists [6,18,19] root for the Gamma distribution for the probability density or Gibbs/exponential distribution for the corresponding cumulative distribution. The high end of the distribution, known as the 'tail', is well described by a power law as observed by Pareto.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Subsequent studies have revealed that the distributions of income and wealth possess some globally robust features (see, e.g., [7]): the bulk of both the income and wealth distributions seem to reasonably fit both the log-normal and the Gamma distributions. Economists have a preference for the log-normal distribution [15,16], while statisticians [17] and physicists [6,18,19] root for the Gamma distribution for the probability density or Gibbs/exponential distribution for the corresponding cumulative distribution. The high end of the distribution, known as the 'tail', is well described by a power law as observed by Pareto.…”
Section: Introductionmentioning
confidence: 99%
“…The crossover point m c is extracted from the numerical fittings. One of the key class of models uses the kinetic theory of gases [21], where the gas molecules colliding and exchanging energy was mapped to agents meeting to exchange wealth, following certain rules [19]. In these models, a pair of agents agree to trade, each save a fraction λ of their instantaneous money/wealth and exchanges a random fraction of the rest at each trading step.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent studies revealed that the distributions of income and wealth possess a number of fairly robust features: the bulk of both the income and wealth distributions seem to reasonably fit both the log-normal and the Gamma distributions (see, e.g., [6]). Economists prefer the lognormal distribution [10,11], while statisticians [12] and physicists [13][14][15][16][17] emphasize on the Gamma distribution for the probability density or Gibbs/ exponential distribution for the corresponding cumulative distribution. However, the high end of the distribution (known as the 'tail') fits well to a power law as observed by Pareto, the exponent known as the Pareto exponent, usually ranging between 1 and 3 (see e.g.…”
Section: Introductionmentioning
confidence: 99%